A POET FOLLOWING SEZAI KARAKOC OR HIS RESURRECTION IDEA: NECAT ÇAVUŞ - İsa IŞIK (Fırat University, 2019)
Resurrection (Diriliş) idea is an Islamic-based idea which Sezai Karakoç, who is one of the most important figure of our literature and thinking world, has systematized. According to resurrection idea, Islamic world must get rid of its current bad situation and must enhance in every field. Karakoç believes that everybody must fulfil their responsibilities for the resurrection to occur. In this context Necat Çavuş, one of the major poets of the generation of 1980, builds his poetica in the track of Sezai Karakoc and 'the idea of resurrection'. Necat Çavuş makes this attitude very clear in his poem books “Bindörtyüzondokuz” and “Amerika”. In his poems, an attitude of a poet who is a fan of resurrection idea and Sezai Karakoç is clearly seen. Sometimes he uses the name of Sezai Karakoç directly and sometimes he calls Sezai Karakoç “my master” in his various poems. In this article, the attitude of a poet who is in the track and thinking of Sezai Karakoç has been aimed.